CCS01.2 A case series of syphilis masquerading as thoracic malignancy. (14th July 2019) - Doctor, Jessica; Nori, Achyuta
Abstract : Background: Infectious syphilis incidence is increasing worldwide, particularly amongst men who have sex with men (MSM). We report a case series of two patients with a rare presentation of syphilitic pneumonitis masquerading as thoracic malignancy. Methods: Patient history review via electronic records. Results: Case 1- 54 year old MSM, HIV diagnosed 2011, CD4 nadir 557 cells/µl, current CD4 861 cells/µl and HIV viral load (VL) undetectable since commencing antiretroviral therapy (ART), presented to emergency department (ED) with pleuritic chest pain and normal oxygen saturation. CT scan demonstrated parenchymal and sub-pleural nodules measuring maximum 13 mm, thought likely to represent malignancy and one lesion had features of an infarct. He started Rivaroxaban in ED and subsequently developed a rash suggestive of evolving syphilis. Rapid plasma reagin (RPR) six weeks after initial presentation was 1:32. Treated with 2 weeks of doxycycline, RPR six weeks later was 1:16 and at five months 1:4. CT scan six weeks post treatment showed almost complete resolution of nodules. Case 2- 38 year old MSM, HIV diagnosed in March 2017, CD4 nadir 65 cells/µl, current CD4 219 cells/µl and VL 109 cells/µl on ART. Kaposi's sarcoma (KS) diagnosed in 2017, involving skin, lymph nodes and spleen, treated to remission with ART alone. Presented in July 2018 with deranged liver function tests. CT scan showed multiple sub-pleural and parenchymal nodules, largest 11 mm, however no progression of lymphadenopathy or clinical progression of cutaneous KS. RPR 1:512 and resolution to 1:16 three months after treatment with intramuscular Benzathine Penicillin. Radiological resolution of lung nodules occurred after 2 months of treatment. Chemotherapy was avoided. Conclusion: Syphilitic pulmonary/pleural nodules resolve with standard antibiotic therapy. Patients with pulmonary nodules usually present to primary care or specialist services where they are investigated for vasculitis/malignancy, but rarely for syphilis. For patients at risk, ruling out syphilis would avoid unnecessary interventions. Disclosure: No significant relationships.